Symposium 4: Perspectives on the International student experience: a review - Reynolds, Michael (Proceedings of the International Conference on Networked Learning, 2008)
There is currently considerable interest in understanding international students’ experience of higher education in English speaking settings and the increase in numbers of students visiting the UK for undergraduate and postgraduate education has made tutors more aware of the problems they and their students encounter – from dealing with language to adjusting to different educational and social customs. A particular aspect of this interest is the interconnection between the international classroom and the application of participative methods in that the increased interaction such methods involve make difference of any kind more significant. This interconnection between difference – whether of gender, nationality, culture – and participative educational methodology - is equally important for us to understand in the context of Networked Learning, especially when it draws on pedagogical traditions with an emphasis on learning as ‘collaborative’, ‘cooperative’, or invokes the concept of ‘community’. The application of these methods usually involves a less directive role for the tutor and a more involving experience for the student. As a consequence, there will be a greater range of possibilities for cultural differences to play a part. However there is a further link. Our ingenuity in designing participative approaches in higher education – including those involving international student groups - may have outrun our understanding of the social and cultural complexities which characterise them. The aim of this paper is to review attempts to research tutors’ and students’ experiences of multinational programmes in order to identify the perspectives which would seem to offer most to those of us who work with international groups of students – including in a networked learning environment. So for example, some authors take a psychological position as a way of understanding students’ responses of frustration, confusion and anxiety when faced with unfamiliar pedagogical approaches or focus on purely educational aspects such as student performance, language difficulties or the impact of stereotypes. Other authors emphasise the interconnectedness of psychological phenomena with social and cultural contexts and important differences - whether as regards gender, religion or politics or place even more emphasis on students’ experience as constructed from social and cultural differences, and of understanding classroom experience as society in microcosm. In an approach that is similar to the one taken in this paper, Archer and Francis have proposed a framework which acknowledges the different perspectives used in addressing the multi-national classroom and argued that these do not simply represent different but equally acceptable alternatives, but that differences are significant in that they predispose educationalists to quite different responses, socially and politically. Archer and Francis propose distinct discourses which can be seen as responses to diversity: for example a compensatory response – as when implicitly positioning students as needing help to conform to the ‘home’ behaviour norms; or multicultural – as when celebrating or subjugating cultural differences in the interests of establishing a collaborative learning environment. The central theme of this paper will be to establish not simply the range of perspectives employed, but to examine whether some are more appropriate in informing our understanding of working with multinational student groups, particularly in a learning environment informed by cooperative principles. As a corollary the paper will consider whether some approaches are – at least if used exclusively – inappropriate, in that they view complex social events through a psychologistic lens.